2012
DOI: 10.1097/pas.0b013e31825a6895
|View full text |Cite
|
Sign up to set email alerts
|

PHOX2B Immunolabeling

Abstract: Peripheral neuroblastic tumors are the most commonly occurring extracranial tumors in children. Although a reliable diagnosis is achievable in the majority of cases, diagnosis of a minority of peripheral neuroblastic tumor cases (especially undifferentiated neuroblastoma) poses a challenge compared with that of other pediatric small round blue-cell tumors. A panel of immunohistochemical markers and fusion transcripts is available for the diagnosis of such tumors, but the markers for neuroblastoma lack specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 39 publications
0
21
0
2
Order By: Relevance
“…All mice implanted with MONC-1-ALK-F1174L cells developed highly malignant undifferentiated tumors, as they strongly expressed the mesechymal/stem marker CD44 and the neural stem/progenitor cell marker nestin, but did not stain for the neuronal marker Ncam1, the adrenergic differentiation marker tyrosine hydroxylase (Th), and the sympathoadrenal marker Phox2b, recently demonstrated as a highly specific marker of undifferentiated NB [30] (Figure 1C). In contrast, MONC-1 cells gave rise to various tumor types, as 3/7 mice developed osteosarcoma with chondrosarcoma components (Figure 1D), 1/7 mouse developed a highly malignant Phox2b − /nestin + undifferentiated tumor (Figure 1E), and 3/7 mice developed Phox2b + /Th − /nestin − undifferentiated NB (Figure 1F).…”
Section: Resultsmentioning
confidence: 99%
“…All mice implanted with MONC-1-ALK-F1174L cells developed highly malignant undifferentiated tumors, as they strongly expressed the mesechymal/stem marker CD44 and the neural stem/progenitor cell marker nestin, but did not stain for the neuronal marker Ncam1, the adrenergic differentiation marker tyrosine hydroxylase (Th), and the sympathoadrenal marker Phox2b, recently demonstrated as a highly specific marker of undifferentiated NB [30] (Figure 1C). In contrast, MONC-1 cells gave rise to various tumor types, as 3/7 mice developed osteosarcoma with chondrosarcoma components (Figure 1D), 1/7 mouse developed a highly malignant Phox2b − /nestin + undifferentiated tumor (Figure 1E), and 3/7 mice developed Phox2b + /Th − /nestin − undifferentiated NB (Figure 1F).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to atypical clinical features, the overall genomic pattern of these NBs revealed atypical segmental patterns. Although histological analysis confirmed the diagnosis of NB, novel histology characterisation using PHOX2B immuno-staining might be useful in this context of atypical NB to help in the diagnosis of undifferentiated types [31]. Indeed PHOX2B immunolabelling has been shown to improve the diagnosis of undifferentiated NB among childhood small round blue-cell tumours with high specificity and sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PHOX2B, whose coding gene is located on chromosome 4p13, is originally found in a NB cell line. It is expressed specifically in the nervous system and has a vital effect on the formation and differentiation of sympathetic neurons and chromaffin cells [34]. In addition, it has been reported that PHOX2B germline mutations, which account for 6% hereditary NBs, are involved in the initiation of NB tumorigenesis [35].…”
Section: Trim11mentioning
confidence: 99%